The importance of sector‐stereotypical images in relation to job pursuit intentions. Issue 4 (26th February 2018) - Peiffer, Mathieu; Habibpour, Mohammad Mahdi; Jegers, Marc; Pepermans, Roland
Abstract : This study broadens the concept of employer image and demonstrates the relevance of applicants' sector image when looking for employment in either nonprofit or for‐profit organizations. We apply the Stereotype Content Model to conceptualize image through perceived competence and warmth and use multilevel analyses on data from final‐year Master's students. Results show the importance of the sector‐stereotypical image and are partially in line with our hypotheses. Job pursuit intentions for specific organizations are predicted by both the organizations' as well as the respective sectors' perceived warmth and competence. Pursuit intentions for the for‐profit sector are predicted only by the image of that sector. However, the intention to pursue employment in the nonprofit sector is predicted by both its competence and warmth as well as by the perceived warmth of its organizations. These findings are discussed in view of a trickle‐down effect and compared to previous findings on sector image among consumers.